WHATSAPP VS PUSH NOTIFICATIONS: UNLOCKING E-GROCERY AFFILIATE PERFORMANCE WITH OPTIMAL STRATEGIC TIMING - Laksmi, Indriana; Sumarwan, Ujang; Munandar, Jono M (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study aims to examine the effect of communication media type and delivery timing on user engagement and behavioral conversion within an e-grocery affiliate program. The research identifies a critical gap in existing literature regarding the comparative effectiveness of personalized external triggers (WhatsApp Blast) versus in-app alerts (Push Notifications) for the domestic housewife segment. The study was conducted using a sample of 500 active female consumers in the "mom and baby" segment of Platform Y in Jakarta during 2025. The analysis method used in this study is Two-Way Analysis of Variance (ANOVA) to test the main and interaction effects between variables. The results indicate that delivery timing (X2) has a significant effect on both engagement (Total Clicks) and conversion (Total Applied), where evening (PM) delivery consistently outperforms morning (AM) delivery due to higher temporal congruence with user leisure time. Communication media type also shows a significant effect, with WhatsApp Blast generating higher conversion performance compared to Push Notifications, confirming that media richness is essential for high-commitment actions. Furthermore, the combination of WhatsApp Blast and Push Notifications produces the most optimal performance. The policy and managerial implications of this study suggest a strategic shift toward evening-based multi-channel communication to maximize affiliate participation and marketing ROI.